The rs738409 (I148M) variant of the PNPLA3 gene and cirrhosis: a meta-analysis - Shen, Jian-Hua (J Lipid Res, 2015)
The human patatin-like phospholipase domain-containing-3 (PNPLA3) gene rs738409 C>G polymorphism is associated with several types of liver disease. The aim of this meta-analysis was to assess the risk of cirrhosis on the basis of rs738409 allele frequency and genotype. Medline, the Cochrane Library, EMBASE, and Google Scholar were searched for prospective and retrospective studies assessing the effect of the rs738409 polymorphism on liver cirrhosis. Seven studies, involving 2,023 patients with cirrhosis, were included. The G allele was associated with a significantly increased risk of cirrhosis versus the C allele [pooled odds ratio (OR) = 1.86, 95% confidence interval (CI) = 1.64–2.12, Z = 9.55, P < 0.001]. Both the GC and GG genotypes were associated with a significantly increased risk of cirrhosis versus the CC genotype (GC vs. CC: pooled OR = 1.73, 95% CI = 1.51–1.98, Z = 7.86, P < 0.001; GG vs. CC: pooled OR = 3.41, 95% CI = 2.77–4.18, Z = 11.65, P < 0.001). There was no evidence of publication bias. Our findings suggest that patients at risk for liver cirrhosis may benefit from PNPLA3 genotyping and thus more intensive monitoring if the rs738409 C>G polymorphism is identified.